Perlindungan Hak Masyarakat Adat Atas Tanah Ulayat Pasca Peraturan Menteri Agraria dan Tata Ruang Nomor 14 Tahun 2024 - Dwi Anang Syukrisna; Rosita Candrakirana; Diana Lukitasari (SENTRI: Jurnal Riset Ilmiah, 2025)
The protection of customary land rights (tanah ulayat) remains one of the most complex and persistent legal issues in Indonesia, particularly after the issuance of the 2024 Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency (Permen ATR/BPN No. 14/2024). This regulation marks a paradigm shift from automatic recognition of customary land based on living customary law to an administrative recognition model requiring formal registration and verification by the state. The topic is important because this shift may significantly affect the legal security, cultural survival, and territorial rights of Indigenous communities who historically rely on traditional norms rather than bureaucratic procedures. This study employs a normative legal research method using statutory, conceptual, and historical approaches to examine the dynamics of customary land regulation and its implications for Indigenous peoples’ rights. Primary legal sources, secondary literature, and constitutional provisions were analyzed qualitatively. The findings show that the administrative-based recognition introduced by Permen ATR/BPN No. 14/2024 reshapes the legal standing of customary land by placing the state as the primary determinant of its validity. While the regulation aims to provide legal certainty, it simultaneously poses risks of marginalization, especially for communities with limited access to administrative processes. The study concludes that the regulation has not fully aligned with principles of justice, living law, or constitutional guarantees. These results highlight the urgent need for regulatory refinement to ensure that administrative mechanisms do not weaken, but rather strengthen, the protection of Indigenous land rights in Indonesia.